Minding the gaps: Using narrative accounts to explore people's experiences of using North Staffs MIND's Adult Counselling Service. Issue 4 (December 2016) - Beaumont, Elaine; Hickey, Anthony Joseph; McAndrew, Sue; Goldman, Stacey; Warne, Tony
Abstract: Introduction: In the UK, almost 50% of illness diagnosed among working age adults is mental distress, with depression and chronic anxiety cited as the two most prevalent psychological illnesses. However, only 24% of those who experience anxiety and depression, consistent with diagnoses, receive National Health Service (NHS) interventions. Effective mental health care is predicated on understanding the lived experiences of those using services in order to provide sensitively attuned therapy. An understanding of the process of counselling and what makes it effective will only be achieved through hearing the voices of service users. However, with regard to counselling, the literature foregrounding the perspectives of those using services remains sparse. Method: This study reports on a qualitative research project, the aim of which was to explore the experiences of people who have used North Staffs MIND's Adult Counselling Service in order to elicit the strengths of and/or opportunities for improving the service. Twelve participants, five males and seven females, were interviewed on a one‐to‐one basis and six themes were identified; Mindful of the Gap; Easing Like Sunday Morning; Magic Moments; Love is in the Air; Lighting up a Future and Following up the Changes: Spreading the Word. Results: Findings suggest the participants in this study found the service beneficial, with therapeutic interventions being tailor‐made to meet the person's needs, and one which ensures a safe environment and compassionate care for those in distress.